Organ transplantation in the vasculitides - Schmitt, Wilhelm; Woude, Fokko J. van der (Current opinion in rheumatology, 2003)
Despite important therapeutic improvements, permanent organ failure may develop in primary systemic vasculitides and affect the heart, the lungs, and especially the kidneys. In systemic vasculitides associated with antineutrophil cytoplasmic antibodies (AASV), end-stage renal failure develops in 20% of cases. Renal transplantation became a beneficial option in these patients, with a graft and patient survival comparable to that in nondiabetic patients. This review summarizes the current knowledge on indications and contraindications for renal transplantation in AASV and discusses the impact of posttransplant immunosuppression on the course of the patients.
Gesehen am 03.06.2022